PSYCOMOTOR PROFILE IN RETROGENESIS: DIFFERENCES BETWEEN ACTIVE AND INACTIVE AGED ADULTS COMPARATIVELY TO THE CHILDREN ONTOGENESIS (Fiep Bulletin - online, 2014)
By facing the current concern with the human aging (increasingly inverting the population pyramid) and the factors that involve this process, the human motricity has been focus of a lot of researches directed to the quality of life of individuals in the aged phase of the life. The aging imposes disfunctions and disintegrations that vary from individual for individual. The field of motricity, which is focused on this study, tries to explain using a Psycomotor Battery (BPM) adapted (FONSECA, 1995), as a means of observation of the motor organism that undergoes this evolutive-involutive process, between the cycles of the ontogenesis (childhood - oldness). Human development is explained from the ontogenetic organization of the cellular formation until the matureness of the puberal organism, which is a continuous process of psycomotor functions (tonicity, balance, laterality, notion of body, space-time organization, fine and global praxis, developed in an ascendant-vertical form, from the simplest to the most complex. This ontogenetic process goes through the deleterious process of the aging that is the retrogenesis of the human development and it can be thought as being a differentiated evolution of the psycomotor profile, being dependent on some factors, amongst which the quality of life and the exercising that they not only allow the motor profit, but motricity as process of evolution psychic and social appropriation.
Keywords: ontogenesis; retrogenesis; motor profile